Answer:
see below
Explanation:
y=6x^2 +2x - 20
a=6 b= 2 c = -20
Quadratic Formula
-b ± sqrt( b^2 - 4ac)
------------------------------
2a
-2 ± sqrt( 2^2 - 4*6(-20))
------------------------------
2*6
-2 ± sqrt( 2^2 - 4*6(-20))
------------------------------
2*6
-2 ± sqrt(484)
------------------------------
2*6
-2 ± 22
------------------------------
12
20/12 = 5/3 -24/12 = -2
solutions are 5/3 and -2
Factoring
0=6x^2 +2x - 20
0 =2( 3x^2 +x - 10)
=2 ( 3x-5) ( x+2)
Using the zero product property
3x-5 = 0 x+2 = 0
3x=5 x =-2
x = 5/3 x = -2
Completing the square
y=6x^2 +2x - 20
Add 20
20=6x^2 +2x
Divide by 6
20/6 = x^2 +2/6x
10/3 = x^2 +1/3x
Take the coefficient of x and divide by 2
1/3 /2 = 1/6
Square it
(1/6) ^2 = 1/36
Add it to each side
10/3 + 1/36 = x^2 +1/3x+ 1/36
120/36 + 1/36 = ( x+ 1/6) ^2
121/ 36= ( x+ 1/6) ^2
Take the square root of each side
sqrt(121/ 36) = sqrt( ( x+ 1/6) ^2)
±11/6 = x+1/6
Subtract 1/6 from each side
-1/6 ±11/6 = x
-1/6 - 11/6 = x -1/6 + 11/6 = x
-12/6 =x 10/6 =x
-2 =x 5/3 =x
Graphing